Trends of waterbirds population changes in Fars province wetlands 1988-2018 - Farhad Hosseini Tayefeh; Mona Izadian; Abbas Ashoori; leyla Jolaee; Elham Ebrahimi (علوم محیطی)
Introduction: Using of waterbirds (waterfowl and waders) census data is common to calculate the size and trend of population changes. Besides, it is important as an indicator of wetlands’ ecological changes in biodiversity conservation. Fars province’s wetlands are one of the most diverse aquatic habitats in Iran where have been severely damaged in recent years due to reduced water levels and habitat changes and consequently, these international wetlands are categorized in the list of Montero as a threatened wetland. In this study, trends of total Waterbirds population changes in Fars province and their main wetlands, including Bakhtegan Basin (Kajjan, Tashk, and Bakhtegan), Parishan and Arjan Plain international wetlands, next to important wetlands of Kaftar, Maharloo and Droudzan Dam Lake have been investigated.  Material and methods: The results of the migratory Waterbirds’ census in Fars province had been obtained from the Department of Environment for about thirty years (1988–2018). Though the population census has been conducted in Fars province since 1967, during the years 1967 to 1987, the census was confined to swans, geese, ducks, and coots, other waterbirds have been added to the bird census since 1988.Data had been analyzed in a long-term period (31-years, 1988-2018) and a short-term period (10-year, 2009-2018) by using RTRIM statistical package. This package has been extracted from Trends & Indices for Monitoring Data (TRIM) in R software. Results and discussion: About 14% of the population and 67% of Iran's waterbirds (116 out of 174 species of Iran) have been related to Fars province, in 31 years ago. The results have been shown a sharp decline in the total population of migratory waterbirds in Fars province with -10.9% slope (0.891 ± 0.0004) per year and also a sharp decline in population with -11% slope for a 10-year period (0.890±0.0001). Only the Maharloo wetlands in the long-term and the Drudzen Dam Lake in the Short-term had a stable population trend, while in other wetlands the trend of decreasing population was moderate to steep. The highest long-term population decline was observed in Parishan wetlands and Arjan plain with -13.9% and -10.1%, respectively. In the short-term, the Parishan wetland had the highest population decline of -10% (0.861 ±0.0001) per year. The highest number of species was observed in the 90s and also in 2004-2009, after this period the species richness of these wetlands decreased. as far as the result shows, the proportion of Bakhtegan and Parishan’s waterbird population was varied from 10% to 88% of the total Fars province’s population. Also, the lowest proportion of the waterbird’s population in these two wetlands was recorded in the last ten years. It seems that drying up of aquatic zones and land-use change were among the most important factors affecting the reduction of population and species richness of waterbirds. As a matter of fact, these wetlands do not have the 5 international criteria of Ramsar wetlands based on the status of the waterbird population. Therefore, need to be prioritized and effective restoration and protection of them in environmental protection programs. Conclusion: In recent years, habitat changes due to aquatic changes and anthropogenic factors have reduced the quality of wetland habitats in Fars province and drastic changes in waterbird populations. Providing the environmental sustainability needed for ecological sustainability, establishing an integrated ecosystem management system, implementing comprehensive wetland management programs, and population monitoring are the most important restoration strategies for the studied wetlands. The results of this study can be used in the management of wetlands ecosystems, preparation and implementation of the restoration plan and also a calculation of damages to wetlands in Fars province.